Online Group Purchasing Environment, the Effects of Price Discounts and Crowd Psychology on Purchasing Behavior - Muhammad Qomarul Huda; A’ang Subiyakto; Aedah Abd Rahman (International Journal of Informatics and Information Systems, 2021)
The goal of this study is to determine the influence of impulsive purchase behavior on mobile marketing, discounts, and consumer lifestyle. The approach used is a combination of quantitative research and an explanation survey. The population for this study is comprised of active internet users who have completed marketplace transactions. The dataset was sampled in a non-probabilistic manner (convenience sampling) and included data from 100 respondents. The results suggested that mobile marketing and promotions had no obvious influence on impulsive purchases made by marketplace customers. Meanwhile, lifestyle has a good influence on the impulsive purchase behavior of marketplace consumers by 35.1 percent. Mobile marketing, incentives, and lifestyle all have a combined influence on the marketplace of 20.9 percent on impulse purchases. While the remaining 79.1 percent is impacted by elements that have not been investigated. This research was conducted using earlier studies as a baseline against which to establish the hypothesis for each variable. The study's design was quantitative, with an emphasis on explanatory research. Convenience sampling was used in this study. This study was successful in determining the effects and interactions associated with impulse purchasing. Discounts, lifestyle, and mobile marketing are integrated and analyzed to see which aspects have the biggest influence.